Mouse paint - Walsh, Ellen Stoll (San Diego : Harcourt, 1989)
Three white mice discover jars of red, blue, and yellow paint and explore the world of color.
"Voyager books.".
Book Links (A.L.A.).
Elem. School Library Collection.
Horn Book.
2.0
K-3
Keywords: Color -- Fiction; Mice -- Fiction; Color -- Fiction; Mice -- Fiction